Sistem Pelacakan Lokasi Pelaporan Petugas Lapangan Irigasi Provinsi Sumatera Barat Berbasis GPS Smartphone dan WebGIS - Budi Sunaryo; Muhammad Ilhamdi Rusydi; Jack Febrian Rusdi; Rifda Suriani; Syafril Daus (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Tracking the location from the side of the report and the position of the reporter in real-time is very much needed in validating the performance of irrigation field officers. The location tracking system represented in smartphone applications, and digital maps are a practical solution for supervisors in monitoring the performance of field officers. The Global Positioning System (GPS) module on Android smartphones and the Web Geographic Information System (WebGIS) are supporting technologies for the system. Each location coordinate on the report will be sent automatically to the MySQL database server, then each coordinate location of the field officer will be sent to the Firebase Realtime Database, coupled with a database synchronization system to handle reports offline when officers are in areas that do not have internet access. Database synchronization plays a role in handling report data stored in the SQLite database on an Android smartphone with a MySQL database server. This system is useful for supervisors in controlling and monitoring the performance of irrigation field officers and can be used as material for decision making. After being implemented in several Irrigation Areas in West Sumatra Province by 113 users consisting of 13 supervisors and 100 field officers, the supervisors can track the location of the report, follow the position of field officers in real-time and send reports offline.